Perception of Farmers Interest Groups (FIGs) of National Agricultural Technology Project about Private Extension services: A micro study in Ahmednagar district of Maharashtra - A.M Chavai,; S.S. Sadaphal,; A.J. Nirban,; G.K. Sawant, (Journal of Agricultural Extension Management, 2025)
No extension system is best for all the places or even for the different stages of development. We have to modify the existing extension system programmes according to the changing needs and resources available with the extension organisations and their beneficiaries. In the present era of economic liberalization and globalisation, we have started talking of private extension